Arms trade as a global international problem - Spalević Žaklina; Bjelajac Željko; Dimitrijević Duško (Međunarodni Problemi, 2013)
The aim of this paper is to highlight the great social danger resulting from uncontrolled trade in arms and military equipment. A large number of terrorist attacks in the world show that uncontrolled arms trade is a growing problem for international security. In order to provide the same protection, the problem of uncontrolled arms and military equipment, which is the major international business, should be viewed from several aspects. To this end, after defining weapons, their production and trade, the authors have presented one of the ways the leading companies in the military-industrial complex provide themselves a market for sale of arms and military equipment, thus creating the conditions that contribute to expanding of their military companies. As the world’s largest exporters of arms and military equipment the United States, Russia and China give a short historical account of their arms trafficking. Then, considering the fact that the amount of weapons would unlikely diminish, the authors have pointed out that states should find a way to control the movement of weapons in the world preventing terrorist to take hold of them.